Periodic perturbations in Shaker K(+) channel gating kinetics by deletions in the S3–S4 linker - Gonzalez, Carlos (National Academy of Sciences, 2001)
Upon depolarization positive charges contained in the transmembrane segment S4 of voltage-dependent channels are displaced from the cytoplasmic to the external milieu. This charge movement leads to channel opening. In Shaker K(+) channels four positively charged arginines in the S4 domain are transferred from the internal to the external side of the channel during activation. The distance traveled by the S4 segment during activation is unknown, but large movements should be constrained by the S3–S4 linker. Constructing deletion mutants, we show that the activation time constant and the midpoint of the voltage activation curve of the Shaker K(+) channel macroscopic currents becomes a periodic function of the S3–S4 linker length for linkers shorter than 7 aa residues. The periodicity is that typical of α-helices. Moreover, a linker containing only 3 aa is enough to recover the wild-type phenotype. The deletion method revealed the importance of the S3–S4 linker in determining the channel gating kinetics and indicated that the α-helical nature of S4 extends toward its N terminus. These results support the notion that a small displacement of the S4 segment suffices to displace the four gating charges involved in channel opening.